2021
DOI: 10.1021/acs.langmuir.1c00525
|View full text |Cite
|
Sign up to set email alerts
|

Hydrated Ionic Liquids Boost the Trace Detection Capacity of Proteins on TiO2 Support

Abstract: Trace detection based on surface-enhanced Raman scattering (SERS) has attracted considerable attention, and exploiting efficient strategies to stretch the limit of detection and understanding the mechanisms on molecular level are of utmost importance. In this work, we use ionic liquids (ILs) as trace additives in a protein-TiO 2 system, allowing us to obtain an exceptionally low limit of detection down to 10 –9 M. The enhancement factors (EFs) were determined to 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
1
9
1
Order By: Relevance
“…For instance, the molecular force of lysozyme with a TiO 2 surface is about 0.86 nN at pH = 7.2, and that for Cyt c with TiO 2 is 1.32 nN, which is in accord with the findings in this work. Meanwhile, the molecular force of Cyt c on the IL-loaded TiO 2 surface is weaker than that on TiO 2 without ILs, which is consistent with the results obtained in this work.…”
Section: Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For instance, the molecular force of lysozyme with a TiO 2 surface is about 0.86 nN at pH = 7.2, and that for Cyt c with TiO 2 is 1.32 nN, which is in accord with the findings in this work. Meanwhile, the molecular force of Cyt c on the IL-loaded TiO 2 surface is weaker than that on TiO 2 without ILs, which is consistent with the results obtained in this work.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Even though they were loaded on the TiO 2 surface, the hydrated cations and anions did change the microenvironment in the solution. Meanwhile, these hydrated ions could form a strong hydration layer on the IL-loaded TiO 2 surface, leading to a decrease in the molecular interaction forces and the total adsorption capacity of proteins …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last step to attach the Cyt c molecules, the tips were immersed in the Cyt c solutions at each ionic strength, then washed with the corresponding ionic strength solutions, and lastly dried with N 2 . Before the adhesion force measurements, the tip’s normal spring constant should be calibrated with the same procedure as that in our previous work ,, in order to transform the measured-load signals from volts (V) into force signals (N). Approximately 100 force–distance curves were measured to obtain the average values of the adhesion force by recording the maximal adhesion force upon retraction.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…), finding that these molecular forces depend both on the properties of the protein and the solid surface and the pH conditions but not the surface roughness. Importantly, these determined molecular forces can be further used as a guideline to design the macroscopic experiments, including protein separation measured by highperformance liquid chromatography, 33 surface-enhanced Raman scattering (SERS)-based protein biodetection, 35 and electron transfer ability of the enzyme tested using an electrochemical biosensor. 34 We found that the magnitude of the ionic strength, induced by the buffer ions, significantly alters the interfacial process performance, while how the ionic strength affects the molecular interaction at the microscale and then influences the performance at the macroscale has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%